Taxonomic notes on a comb-footed spider, Yunohamella mneon (Bösenberg & Strand, 1906), stat. rev. (Araneae: Theridiidae) in East Asia - Suzuki, Yuya; Lee, Jun-Gi; Kumada, Ken-Ichi (Zootaxa, 2025)
Platnickina mneon (Bösenberg & Strand, 1906) is a theridiid species originally described based on a female specimen collected in Saga Prefecture, Kyushu, Japan. Although P. mneon was recently considered a junior synonym of Yunohamella lyrica (Walckenaer, 1841), the two species can be clearly distinguished by body coloration and markings, genital morphology, and molecular data. Based on these findings, we reestablish P. mneon as a valid species under the genus Yunohamella, Yunohamella mneon stat. rev. Based on a partial mitochondrial COI gene sequence analysis, our study also revealed that the female of Y. mneon stat. rev. is conspecific to the male currently associated with Yunohamella varietas Lee & Kim, 2021 and we propose Y. mneon stat. rev. = Y. varietas syn. nov. The species is compared with Y. lyrica and Platnickina adamsoni Berland, 1934 and molecular data of Yunohamella species in East Asia are presented, with a summary of the taxonomic history of relevant species in Japan and Korea.